Estetika Fotografi Liam's World Karya Erin Lefevre - Rahardian, Adinatasya Luthfiyyah; Saleh, Sukmawati (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2024)
Aesthetics or beauty is found in every photographic work. Apart from the visual aspect, the meaning of a photo is also important in photography aesthetics. Erin Lefevre is a documentary photographer who created a collaborative photo series project with her younger brother who was diagnosed with autism, named Liam. This research examines eight of Erin's photographs from the Liam's World photo series. Qualitative methods and photography aesthetic theory were used in this research. The focus of the analysis lies in the ideational and technical aspects to find the meaning contained in the representation of the daily life of children with autism. The results of the study show that photographers can capture the unique world of autistic children with good visual elements, apart from producing aesthetic work they can also provide in-depth insight into the life experiences of children diagnosed with autism. So, it is hoped that documentary photography will be able to change people's perceptions about autism